Answer:

Method 1:

A = [(k + 1)/k ]^k

B = [(k/(k - 1)]^(k - 1)

Apply PMI now to get : A > B

Method 2:

Solution:

(1+ 1/n)^n = e ~ 2.78xx.. as n tends to infinity.

Now its an increasing function because just check for

A = (1 +1/2)^2 and B= (1 +1)^1 ==> A= 9/4= 2.25 and B=2. So clearly A>B here.

So, as the function is increasing so, it will also satisfy for our given A and B. i.e., A>B here.

f(x)= (1 + 1/x)^x is alwz an increasing function. and as it is increasing function so, if x> y then f(x) > f(y) alwz.

It also satisfies from here.